Prediction modelling of exhaust characteristics of a marine engine for SCR urea dosing calibration. (27th January 2020) - Zhang, Zhuo; Shi, Mingwei; Yin, Zibin; Wu, Defeng; Dai, Leyang
The International Maritime Organisation (IMO) issued Annex VI of the MARPOL Convention to control the serious exhaust pollution of marine diesel engines, specifying the NOx emission limitation requirements. In this paper, the exhaust characteristics of a marine diesel engine were tested, and the exhaust characteristic model was established by a BP neural network, which has been verified via learning ability and generalisation ability. The relative errors of the exhaust flow, NOx concentration and exhaust temperature prediction are within 6%, which can be used to predict the exhaust performance of a marine diesel engine in steady state. The calibration for urea dosing of an SCR system was based on an ammonia-nitrogen ratio of 1:1, whose data are predicted by the exhaust characteristic model.